PELATIHAN ETIKA KOMUNIKASI POLITIK RUANG MEDIA SOSIAL: MEMBACA PROFIL LAWAN POLITIK - Hamzah, Hamzah; Aziz, Ervan (Lembaga Penelitian dan Pengabdian Masyarakat STISIPOL Candradimuka Palembang, 2020)
Political ethics training in communicating in the media sphere can be an illustration of the profile of political opponents. In this study data collection was carried out by means of observation, documentation and interviews with selected informants. Ethics and etiquette both concern behavior and regulate human behavior normatively (giving norms to human behavior and thereby stating what humans should or should not do). Communication is a social process in which individuals use symbols to create and interpret meaning in their environment. Five (5) key terms in the perspective of communication, namely: social, process, symbol, meaning and environment.